Analiza błędów w przekładzie unijnych aktów normatywnych na przykładzie Council Regulation (EC) no 1346/2000 of 29 May 2000 on Insolvency Proceedings. - Nowak, Paulina (Investigationes Linguisticae, 2006)
This paper deals with the analysis of mistakes and errors in the translation of the Council Regulation (EC) no 1346/2000 of 29 May 2000 on insolvency proceedings from English into Polish. This article presents a selection of examples from English and French versions together with their incorrect translations into Polish by UKIE with the author?s suggestions of correct equivalents. There is also a short description of the spotted types of language and translation method applied (or no translation method applied), syntactic and grammatical differences in Polish and English, as well as culturally-conditioned differences in Polish and English legal realities.